See I told you I was taking it! - attitudes of adolescents with asthma towards a device monitoring their inhaler use: Implications for future design - Howard, Sam; Lang, Alexandra. R.; Sharples, Sarah; Shaw, Dominick E. (Elsevier, 2016)
Adherence to treatment in asthma is often poor, particularly in adolescents and children where the condition is most prevalent. Electronic monitoring devices have shown potential for improving inhaler use, yet little research has considered the attitudes of patients towards these devices. We gave seven adolescents with asthma an electronic monitoring device to use for one month and collected their views on important issues including monitoring and data sharing. Our results showed that participants felt positively about using the data to demonstrate responsibility for their condition to both their parents and medical professionals, but expressed concern for the attention the device’s appearance could draw to them and their asthma. This paper considers the positive and negative perceptions of this novel device and provides new insight into the attitudes of adolescents towards inhaler monitoring, as well as future directions for design and development of monitoring devices for asthma and other chronic medical conditions.